Knockdown of Mitochondrial Uncoupling Proteins 1 and 2 (AtUCP1 and 2) in Arabidopsis thaliana Impacts Vegetative Development and Fertility - Arcuri, Mariana De Lara Campos [UNESP]; Nunes-Laitz, Alessandra Vasconcellos [UNESP]; Lima, Rômulo Pedro Macêdo [UNESP]; Barreto, Pedro; Marinho, Andressa Nagatani [UNESP]; Arruda, Paulo; Maia, Ivan G [UNESP] (Oxford University Press (OUP), 2021)
Mitochondrial uncoupling proteins (UCPs) are mitochondrial inner membrane proteins that dissipate the proton electrochemical gradient generated by the respiratory chain complexes. In plants, these proteins are crucial for maintaining mitochondrial reactive oxygen species (ROS) homeostasis. In this study, single T-DNA insertion mutants for two (AtUCP1 and AtUCP2) out of the three UCP genes present in Arabidopsis thaliana were employed to elucidate their potential roles in planta. Our data revealed a significant increase in the Adenosine triphosphate (ATP)/Adenosine diphosphate (ADP) ratios of both mutants, indicating clear alterations in energy metabolism, and a reduced respiratory rate in atucp2. Phenotypic characterization revealed that atucp1 and atucp2 plants displayed reduced primary root growth under normal and stressed conditions. Moreover, a reduced fertility phenotype was observed in both mutants, which exhibited an increased number of sterile siliques and a lower seed yield compared with wild-type plants. Reciprocal crosses demonstrated that both male fertility and female fertility were compromised in atucp1, while such effect was exclusively observed in the male counterpart in atucp2. Most strikingly, a pronounced accumulation of hydrogen peroxide in the reproductive organs was observed in all mutant lines, indicating a disturbance in ROS homeostasis of mutant flowers. Accordingly, the atucp1 and atucp2 mutants exhibited higher levels of ROS in pollen grains. Further, alternative oxidase 1a was highly induced in mutant flowers, while the expression profiles of transcription factors implicated in gene regulation during female and male reproductive organ/tissue development were perturbed. Overall, these data support the important role for AtUCP1 and AtUCP2 in flower oxidative homeostasis and overall plant fertility.
Keywords: Arabidopsis thaliana •; Mitochondria; Mitochondrial uncoupling protein; Plant fertility; UCP